2017
DOI: 10.1155/2017/5832824
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment with PPARγLigand and Its Specific Inhibitor GW9662 Downregulates BIS and 14-3-3 Gamma, Inhibiting Stem-Like Properties in Glioblastoma Cells

Abstract: PPARγ is a nuclear receptor that regulates differentiation and proliferation and is highly expressed in many cancer cells. Its synthetic ligands, such as rosiglitazone and ciglitazone, and its inhibitor GW9662, were shown to induce cellular differentiation, inhibit proliferation, and lead to apoptosis. Glioblastoma is a common brain tumor with poor survival prospects. Recently, glioblastoma stem cells (GSCs) have been examined as a potential target for anticancer therapy; however, little is known about the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…31 Recent studies have revealed that GW9662, with or without PPARγ ligands, could be a potential therapeutic strategy targeting glioblastoma stem cells. 55,56 In accordance with the knockdown assays, our results revealed that GW9662 could inhibit the proliferation of BCa 5637, T24 and UM-UC-3 cells in a time and dose-dependent manner. The invasion and migration rate were also reduced in BCa cells treated with GW9662, with reversed EMT markers, which could suggest tumour malignancy.…”
Section: Discussionsupporting
confidence: 77%
“…31 Recent studies have revealed that GW9662, with or without PPARγ ligands, could be a potential therapeutic strategy targeting glioblastoma stem cells. 55,56 In accordance with the knockdown assays, our results revealed that GW9662 could inhibit the proliferation of BCa 5637, T24 and UM-UC-3 cells in a time and dose-dependent manner. The invasion and migration rate were also reduced in BCa cells treated with GW9662, with reversed EMT markers, which could suggest tumour malignancy.…”
Section: Discussionsupporting
confidence: 77%
“…Overexpression of PPARγ is also a hallmark of GBM cells [33] and it has been documented that the PPARγ agonists thiazolidinediones and Fmoc-L-Leucine inhibit growth, proliferation, and induce apoptosis in various human glioblastoma cells in vivo, and thus may be regarded as a potential agents for GBM therapy [34,35,36,37,38,39]. The obvious conclusion is to combine both factors to potentiate anti-glioma effects [31].…”
Section: Introductionmentioning
confidence: 99%
“…17 Higher levels of 14-3-3 are also evident in GSC. 18 As indicated above, both miR-7 and miR-451 can repress 14-3-3ζ in both tumour and nonneoplastic cells. 8,14,19 The loss of 14-3-3 sensitizes GBM/GSC to apoptosis as well as preventing NAS synthesis, thereby preventing any trophic effects of NAS via the TrkB.…”
Section: -3-3mentioning
confidence: 85%